The Prevalence of Paroxysmal Nocturnal Hemoglobinuria Clone in Adult Patients with Idiopathic Pulmonary Hypertension - Mesut Ayer; Tayfun Elibol; Ümit Yaşar Sinan; Cengiz Bal; Mehmet Serdar Küçükoğlu (Haseki Tıp Bülteni, 2018)
Aim: Paroxysmal nocturnal hemoglobinuria (PNH) a is a clonal disorder that may lead to several conditions such as thromboses, Budd-Chiari syndrome, renal failure, impotence, and pulmonary hypertension (pHT). Since the presentation of PNH may be occult, monitoring for clonal evolution is recommended in certain situations including aplastic anemia, Myelodysplastic syndrome, and unexplained cytopenia, and thrombosis. The prevalence of PNH clone in patients with idiopathic pHT is unknown. We designed a study to determine the prevalence of PNH clone in patients with idiopathic pHT, since it may be the first isolated presentation of the disease.